La politisation de la religion au temps de la question romaine dans l’Ouest français (1860-1870) - Arthur Hérisson (Mélanges de la Casa de Velázquez)
In France, throughout the 19th century, the politicisation of Catholics was largely the result of conflicts between them and a state whose modernisation was marked by secularisation. The mobilisation against the Italian policy of Napoleon III illustrates this situation well. Such mobilisation was marked by a continued appropriation by Catholics of modern forms of politics. However, this appropriation was not just a passive process of taking up repertoires of action already used by others; on the contrary, it took specific forms, linked to the characteristics of Catholicism at the time, and in particular to the refusal of an absolute separation between politics and religion.Using the case of western France as a starting point, we propose to show how the politicisation of Catholics at the time of the Roman question was able to take on original forms, alongside classic political practices, testifying to an interpenetration of the political and religious spheres.